Chinese Responses to U.S. Military Transformation and Implications for the Department of Defense - Mulvenon, James C. (RAND Corporation, 2006)
For the past decade, Chinese military strategists have keenly observed the changes in U.S. national strategy and military transformation. This report examines the constraints, facilitators, and potential options for Chinese responses to U.S. transformation efforts and offers possible U.S. counterresponses (particularly in light of whether Taiwan moves toward or away from formal independence).